Implementation of tunable resonators in planar groove gap waveguide technology. Issue 4 (22nd May 2022) - Oyedokun, Titus; Geschke, Riana H.; Stander, Tinus
Abstract: We present a tunable planar groove gap waveguide (PGGWG) resonant cavity at Ka -band. The cavity demonstrates varactor loading and biasing without bridging wires or annular rings, as commonly is required in conventional substrate-integrated waveguide (SIW) resonant cavities. A detailed co-simulation strategy is also presented, with indicative parametric tuning data. Measured results indicate a 4.48% continuous frequency tuning range of 32.52–33.98 GHz and a Qu tuning range of 63–85, corresponding to the DC bias voltages of 0–16 V. Discrepancies between simulated and measured results are analyzed, and traced to process variation in the multi-layer printed circuit board stack, as well as unaccounted varactor parasitics and surface roughness.